Differential flatness based flight control of tilt-rotor VTOL aircraft - Joseph, Emmanuel Biju (Cranfield University, 2021)
Urban Air Mobility (UAM) is identified as the future of mobility, and several airframes are being trialled to fit air transport within modern cities. Speed and efficiency are the primary requirements deliberated for UAM Vertical Take-off and Landing (VTOL) aircraft, and configurations incorporating tilt-rotors and tilt-wings have been identified as viable solutions. For quadrotors and robotics, control techniques leveraging the differentially flat property of system dynamics have achieved significantly improved tracking performance and motivated the application of this control technique for VTOL aircraft. This study proposes a novel control architecture based on the differential flatness property of aircraft kinematics, to improve controller performance for autonomous flight. A conceptual validation of the proposed technique was implemented on a Planar VTOL (PVTOL) model as a precursor to the research. Consequently, an architecture for implementing the concept in tilt-rotor VTOL aircraft (Aston Martin Vision Volante) was devised, implemented, and tested. The control architecture achieved the speculated performance improvements and lays foundation for further research and development into the proposed control technique.
Whidborne, James F. - Associate Supervisor
Keywords: UAM; Control Allocation; Control Architecture; tilt-rotors; tilt-wings; aircraft kinematics